Economic Implications and Management of Bovine Tuberculosis in Fiji: Promoting Decent Work and Economic Growth - Igbal, Mohammed Rasheed; Iqbaal, Ubaadah Bin; Kumar, Shaista Snehal; Magiri, Royford Bundi; Kumar, Saleshni (Journal of Ecohumanism, 2024)
Fiji is one of the Pacific countries highly affected by Bovine Tuberculosis. Bovine Tuberculosis (bTB) is globally critical because of its effects on animal production. A Brucellosis and Tuberculosis Eradication and Control (BTEC) program was initiated in Fiji during the 1980s and has since been supported by government financing and industry participation. Bovine Tuberculosis is a persistent bacterial illness of animals and people caused by Mycobacterium bovis. In many nations, bovine Tuberculosis is a significant irresistible illness among cows, other domestic animals, and specific natural life populaces. Bovine Tuberculosis in Fiji leads to reduced opportunities for local trades and a lower production system because of ill animals and pre-mature cull of potential production stock. The bTB conditions in Fiji have become a rising concern for the stakeholders of livestock industries as the stock culling further teases lower milk production in the nation. The Biosecurity Authority of Fiji also implemented and raised awareness for farmers to consider BTEC program strategies to reduce the risk of bTB. The plan was further finalized and refined by the Ministry of Agriculture in early 2018. The proposal of this strategy involved recommendations and reviews on the hygiene of meat, control methods of bTB and selection of diagnostic tests to encourage and strengthen BTEC program strategies in Fiji.